INNOVATIVE APPROACHES TO TEACHING ENGLISH IN HIGHER EDUCATION - Bekchanova Khushbaroy (Bright Mind Publishing, 2025)
Modern English language teaching (ELT) requires a shift from traditional, teacher-centered instruction toward interactive, technology-enhanced, and competency-based approaches. This article examines several innovative strategies that enhance learner motivation, improve communication skills, and promote autonomous learning. The study highlights the role of communicative language teaching, project-based learning, technology integration, gamification, differentiated instruction, formative assessment, and cultural awareness in contemporary classrooms. The paper argues that these approaches create effective learning environments and better prepare students for academic and professional contexts.
Keywords: English language teaching, communicative approach, gamification, higher education, project-based learning, technology integration, learner autonomy.